Parents’ nutrition knowledge, perceived barriers and enablers, and healthy-eating attitudes associated with children’s adherence to the Mediterranean diet: the DELICIOUS project - Castellano, Sabrina; Choo, Wen Rui; Rosi, Alice; Abril Mera, Tania; Scazzina, Francesca; Giampieri, Francesca; Frias-Toral, Evelyn; Abdelkarim, Osama; Aly, Mohamed; Ammar, Achraf; Pons, Juancho; Vázquez-Araújo, Laura; et al. (Frontiers in Nutrition, 2026)
ObjectiveChildren’s dietary choices are influenced by several factors, including parents’ modeling. The relation between parents’ psychosocial factors and their children’s level of adherence to the Mediterranean diet were explored.MethodsFood literacy, perceived barriers and enablers, and healthy-eating attitude following the Capability, Opportunity and Motivation (COM-B) model for behavioral change were evaluated in 2,011 participants in the DELICIOUS (UnDErstanding consumer food choices & promotion of healthy and sustainable Mediterranean Diet and LIfestyle in Children and adolescents through behavIOUral change actionS) project. Adherence to the Mediterranean diet was assessed through the KIDMED questionnaire. Beta coefficients and standard errors (SEs) were calculated through linear regression analyses.ResultsPost-adjustment for potential confounding factors, results showed significant positive correlation between children’s adherence to the Mediterranean diet and parental food literacy [β (SE) = 0.180 (0.011)], perceived barriers and enablers [β (SE) = 0.135 (0.009)], and healthy-eating attitudes (divided into five constructs) [β (SE) = 0.069 (0.030), β (SE) = 0.037 (0.029), β (SE) = 0.162 (0.017), β (SE) = 0.147 (0.010), β (SE) = 0.158 (0.011)]. Individual dietary components of the Mediterranean diet were also associated with various psychosocial factors.ConclusionThese results confirm the importance of parental food literacy, perceived enablers and barriers to healthy-eating, health-eating attitude in their children’s adherence to the Mediterranean diet.